LncRNA DHRS4-AS1 Inhibits the Stemness of NSCLC Cells by Sponging miR-224-3p and Upregulating TP53 and TET1 - Yan, Fei; Zhao, Wei; Xu, Xiaoyue; Li, Chenchen; Li, Xiaoyou; Liu, Siwen; Shi, Lin; Wu, Yuan (Frontiers in Cell and Developmental Biology, 2020)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death. This study aimed to examine the roles of DHRS4-AS1/miR-224-3p signalling in the cancer cell stemness of NSCLC. Real-time PCR showed that DHRS4-AS1 was downregulated in cancerous tissues, and bioinformatics analysis revealed that high DHRS4-AS1 expression indicated a good prognosis for NSCLC patients. Sphere and colony formation assays showed that DHRS4-AS1 overexpression significantly suppressed NSCLC cell colony formation and stem cell-like properties. DHRS4-AS1 also abrogated the expression of OCT4, SOX2, CD34, and CD133, markedly inhibited the expression of epithelial-mesenchymal transition (EMT)-related factors, N-cadherin, ZEB1, and Vimentin, and increased E-cadherin expression in spheres. Furthermore, luciferase reporter assays and real-time PCR analysis demonstrated that DHRS4-AS1 and miR-224-3p were antagonistically repressed in NSCLC cells. RNA immunoprecipitation (RIP) analysis revealed that DHRS4-AS1 interacted with miR-224-3p. DHRS4-AS1 partially reversed the miR-224-3p-decreased TP53 and TET1, resulting in the inhibition of tumor growth in vivo. Finally, TP53 and TET1 were antagonistically regulated by DHRS4-AS1 and miR-224-3p in NSCLC cells. In conclusion, TP53- and TET1-associated DHRS4-AS1/miR-224-3p axis is an essential mechanism by which NSCLC modulates cancer cell stemness.